Heavy-quark dominance and fine structure of excited heavy baryons $$Σ _{Q}$$ Σ Q , $$Ξ '_{Q}$$ Ξ Q ′ and $$Ω _{Q}$$ Ω Q - Zhen-Yu Li; Guo-Liang Yu; Zhi-Gang Wang; Jian-Zhong Gu (European Physical Journal C: Particles and Fields)
Abstract In the framework of the relativized quark model, the calculation of spin-orbit interactions is improved by considering the contribution from the light-quark cluster in a singly heavy baryon. It modifies the energy level splitting of the orbital excitation significantly and causes the emergence of fine structures for $$Σ _{Q}$$ Σ Q , $$Ξ '_{Q}$$ Ξ Q ′ and $$Ω _{Q}$$ Ω Q baryons. Based on this improvement, we systematically analyze the fine structures and retest the heavy quark dominance mechanism. This mechanism is found to be violated in the 1P-wave states of the $$Σ _{c}$$ Σ c , $$Ξ '_{c}$$ Ξ c ′ and $$Ω _{c}$$ Ω c baryons although it remains effective overall, which may help to understand the nature of the heavy quarks and strong interactions. With the predicted fine structures, we make the precise assignments of those observed heavy baryons which once could not be accurately explained due to their close mass values. The method used in this work is instructive and applicable for the study of more complex exotic hadrons, such as the heavy tetraquarks and pentaquarks.